UNISMA BEKASI SEBAGAI PUSAT SISTEM MANAJEMEN PENGETAHUAN: SEBUAH GAGASAN - Khoir HS, Abdul (Turats, 2015)
This paper is an idea to increase the role of Islamic University "45" (UNISMA) Bekasi as the Centre of Knowledge Management System. Optimization of the role will be increasingly important UNISMA existence when capable of being a facilitator and mediator of the growing culture of knowledge sharing culture among academic society that has implications for opening up opportunities to publish various ideatau research management. Knowledge Management (KM) is a technique to organize knowledge in the organization. The goal is to accelerate the innovation by improving the effectiveness and efficiency of absorption of knowledge through knowledge sharing process. Product knowledge sharing is managed through a knowledge management system known term OKMS (Organization Knowledge Management System) which underlie management process includes 4 main functions, namely; using knowledge, finding knowledge, creating knowledge, and packaging knowledge. The process of uncovering tacit knowledge into explicit knowledge sehigga can be transferred to others. Given the background of the formation and establishment UNISMA and the human resources are multi-disciplinary background, the idea to make UNISMA as a center of knowledge management system the best choice.